The restrictions on the use of weapons under international law: the case of depleted uranium - Issa, Aqila Hadi; Abdul Wahab, Harlida; Abdullah, Nor Anita (Medwell Journal, 2016)
Depleted uranium weapon is relatively one of the modern weapons.It has been associated with the appearance of nuclear weapon due to its waste of the nuclear fuel.In addition, nuclear weapon is considered as being a new weapon as well as depleted uranium.The current study focuses on the extent of applicability of the restrictions concerning the use of weapons, specifically the depleted uranium weapon in which it should be banned.Currently, there is no international convention banning the use of depleted uranium weapon in spite of its serious impacts upon human life, the environment and successive generations. This poses a noticeable controversy over the subordination of restrictions with respect to the use of weapons under international law. Hence, this study has a significant implication for the international community to undertake actions regarding the use of depleted uranium weapon in wars to provide legal protection for humans and the environment as well as to keep international peace and security.A conclusion and a contribution of scholars in the field of law concerning this particular issue are presented accordingly.